2022
DOI: 10.3389/fimmu.2021.827946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phospholipids on Growth Performance, Digestive Enzymes Activity and Intestinal Health of Largemouth Bass (Micropterus salmoides) Larvae

Abstract: While the beneficial roles of dietary phospholipids on health status and overall performances of fish larvae have been well demonstrated, the underlying mechanisms remain unclear. To address this gap, the present study was conducted to investigate the effects of dietary phospholipids on growth performance, intestinal development, immune response and microbiota of larval largemouth bass (Micropterus salmoides). Five isonitrogenous and isolipidic micro-diets were formulated to contain graded inclusion levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Studies have revealed the beneficial effects of PLs in diet emulsification (Koven et al, 1993), fatty acid absorption (Fontagné et al, 2000;Hadas et al, 2003), digestive enzyme activities (Gisbert et al, 2005), intestinal lipid transportation (Lin et al, 2018) and microbiota composition (Wang et al, 2021). However, no consensus has been reached about the relationship between dietary intact PLs and intestinal morphology at the fish larval stage.…”
Section: Dietary Phospholipids Improved Intestinal Morphologymentioning
confidence: 99%
“…Studies have revealed the beneficial effects of PLs in diet emulsification (Koven et al, 1993), fatty acid absorption (Fontagné et al, 2000;Hadas et al, 2003), digestive enzyme activities (Gisbert et al, 2005), intestinal lipid transportation (Lin et al, 2018) and microbiota composition (Wang et al, 2021). However, no consensus has been reached about the relationship between dietary intact PLs and intestinal morphology at the fish larval stage.…”
Section: Dietary Phospholipids Improved Intestinal Morphologymentioning
confidence: 99%
“…It is suggested that the specific requirement of phospholipids in fish larvae mainly results from the low capacity of enterocytes for the biosynthesis of phospholipids idella; Chen et al, 2015), juvenile hybrid snakehead (Lin et al, 2018) and blunt snout bream (Megalobrama amblycephala; Li et al, 2015) clarified the necessity of low-level endogenous phospholipids inclusion in compound feed based on growth performance. Previous study in our laboratory has well clarified that largemouth bass larvae have a relative higher phospholipids requirement than other freshwater fish (Wang et al, 2021), which makes the hypothesis reasonable that phospholipids is essential for early juvenile largemouth bass. However, in this study, the inclusion of exogenous phospholipids did not produce any significant difference in growth performance of early juvenile largemouth bass, which was consistent with some previous studies in juvenile large yellow croaker (Feng et al, 2017), Atlantic salmon (Taylor et al, 2015) and hybrid grouper (Huang et al, 2022).…”
Section: Discussionmentioning
confidence: 69%
“…Largemouth bass (Micropterus salmoides), a freshwater carnivorous fish, has become one of the important economic farmed fish in China. Previous study in our laboratory has determined the optimal dietary phospholipids, at least 9.29%, of larval largemouth (Wang et al, 2021), which was relatively higher than other freshwater larvae (2%-5%; Tocher et al, 2008). It is unclear whether early juvenile largemouth bass has a relative higher requirement for phospholipids.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hence the lipid deposition and available energy required for the growth increase [ 45 ]. The increased growth rate can be related to improved feed intake and utilization of SBL addition [ 46 ]. Indeed, the study showed a reduced FCR in striped catfish with SBL feeding.…”
Section: Discussionmentioning
confidence: 99%